SIGNS AND SYMBOLS OF THE HUTSUL TEXT: CENTRALITY OF THE CARPATHIANS AND CORDISM OF HUTSULSHYNA IN THE UKRAINIAN LITERATURE OF THE XIXth – EARLY XXth CENTURY - Васильчук, М. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article examines the attributes and symbolism of the Hutsul text on the example of Ukrainian classical literature texts of the XIXth – early XXth c.. The author introduces new notions of centrality of the Carpathians and cordism of Hutsulshchyna into a scientific circulation, substantiates their employment for denoting the phenomena characteristic of the Ukrainian fiction on the theme of the Carpathians.